ANALISIS KAJIAN KITAB KLASIK ARAB: EDUKASI AKHLAK PRASEKOLAH PERSPEKTIF ABDULLAH NASHIH ULWAN - Devi vionitta wibowo; Ririn Dwi Wiresti (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
The decline of morals in the present has triggered the emergence of a generation of preschool children who deserve to be watched out for. The existence of online games, uneducative books, and even pornographic sites is the trigger for all this. The purpose of this article is none other than to present a new scientific study regarding the study of morals for preschool children in the book Tarbiyatul Aula Fil Islam by Abdullah Nashih Ulwan. Researchers analyzed this book with a qualitative literature method in the form of content analysis of moral education content for preschool children, then analyzed based on the curriculum used in preschool learning. The results of the study state that there is a moral education environment in the book which consists of the realm of faith which requires children to know their Rabb, the domain of their personality which focuses on developing honesty, friendly learning, avoiding lies, and manners towards parents. All this is done in a supportive and positive social environment, namely the family is the first step in planting it. Parents instill children in order to have the nature of help, sympathy for others. Its application can be applied through the method of advice, demonstration, habits that become routine, as well as punishment in supervision. The implementation of moral education in the book into the 203 PAUD curriculum at Core Competency number 1, 2, which can refer to the development of children's moral behavior.Kemerosotan akhlak di masa kini memicu timbulnya generasi anak prasekolah yang patut untuk diwaspadai. Adanya game online, buku tidak mendidik, bahkan situs pornografi menjadi pemicu semua ini. Tujuan dari artikel ini tidak lain adalah meyajikan kajian kelimuan baru mengenai kajian akhlak bagi kanak prasekolah dalam kitab Tarbiyatul Aula Fil Islam karya Abdullah Nashih Ulwan. Peneliti menganalisis kitab ini dengan metode kualitatif kepustakaan berupa analisis konten isi edukasi akhlak bagi kanak prasekolah, kemudian dianalisis berdasarkan kurikulum yang digunakan dalam pembelajaran Prasekolah. Hasil penelitian menyatakan bahwa adanya ruang lingkung edukasi akhlak dalam kitab yang terdiri dari ranah keimanan yang mengharuskan anak untuk mengetahui Rabbnya, ranah kepribadiannya yang berfokuskan pada pengembangan pembelajaran kejujuran, ramah, menghindari kebohongan, sopan santun terhadap orangtua. Semua itu dilakukan pada lingkungan sosial yang mendukung dan positif, yaitu keluarga langkah awal untuk penanamannya. Orangtua menanamkan anak agar memiliki sifat tolong menolong, simpati kepada orang lain. Pengaplikasiannya dapat diterapkan melalui metode nasehat, percontohan, kebiasaan yang menjadi rutinitas, srta hukuman dalam pengawasaan. Adanya implementasi edukai akhlak dalam kitab ke dalam kurikulum 203 PAUD pada Kompompetensi Inti nomer 1,2, yaitu dapat mengacu pada pengembangan prilaku moralitas anak.